2022
DOI: 10.1098/rsbl.2021.0551
|View full text |Cite
|
Sign up to set email alerts
|

Climate change winners and losers among North American bumblebees

Abstract: Mounting evidence suggests that climate change, agricultural intensification and disease are impacting bumblebee health and contributing to species’ declines. Identifying how these factors impact insect communities at large spatial and temporal scales is difficult, partly because species may respond in different ways. Further, the necessary data must span large spatial and temporal scales, which usually means they comprise aggregated, presence-only records collected using numerous methods (e.g. diversity surve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(58 citation statements)
references
References 54 publications
(91 reference statements)
1
48
0
Order By: Relevance
“…This all shows that changes in insect abundance and diversity are complex, heterogenous and do hardly correlate amongst taxa (van Klink et al 2022). All studies revealed winners and losers among insect taxa (Jackson et al 2022), but their proportion varied. Each study contributes therefore to the general body of knowledge about changes in species richness and abundance of arthropods in general.…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…This all shows that changes in insect abundance and diversity are complex, heterogenous and do hardly correlate amongst taxa (van Klink et al 2022). All studies revealed winners and losers among insect taxa (Jackson et al 2022), but their proportion varied. Each study contributes therefore to the general body of knowledge about changes in species richness and abundance of arthropods in general.…”
Section: Introductionmentioning
confidence: 75%
“…All these factors were highly correlated with the year of sampling (Online Appendix S11), thus confounding factors for a comparative analysis. Nevertheless, the effects of climate change should also be considered as explanatory factors for the observed differences in species richness, abundance and biomass, although effects may even be species specific (Jackson et al 2022). Beside the specific weather conditions in the study years (Online Appendix S10) also lag effects (weather conditions in preceding years, frost days in previous winter) could have affected our catches.…”
Section: Discussionmentioning
confidence: 99%
“…Those species active during mid‐ to late‐summer extreme heatwaves, however, are likely to face multiple periods of prolonged heat stress each year. Such events may lead to local extinctions or rapidly advancing climate envelopes (Marshall et al, 2020) Whether insect benefits and detriments to a hotter climate will balance, however, is an open question (Lehmann et al, 2020; but also see Jackson et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The overall abundance of moths and butterflies remains stable along pollution gradients because the abundances of several Lepidoptera species increase sharply near the polluters (in line with the pattern discovered by meta-analysis [19]), while the populations of other species decline (Figure 4). The among-species variation discovered in the responses to pollution (and to associated environmental stressors) is likely a common trait of insects, because both winners and losers have been previously identified by analyses of climate-driven changes in communities of dragonflies [37], moths [38], and bumblebees [39]. Importantly, ours is the first study to demonstrate that the responses of individual species to industrial pollution were consistent between the two polluted regions, Nikel/Zapolyarnyy (this study) and Monchegorsk [18], despite the substantial differences in their pre-industrial environments and pollution histories.…”
Section: Spatial Patterns In Abundance and Diversitymentioning
confidence: 99%